AN ANALYSIS OF GRAMMATICAL ERRORS OF USING GOOGLE TRANSLATE FROM INDONESIA TO ENGLISH IN WRITING NARRATIVE TEXT - Azura Srikandi (XXXXXXXX, 2023)
This study focuses on the grammatical errors made by Google Translate in translating narrative text from Indonesian to English.The narrative text is a text written by class X culinary arts studentsat SMK Tunas Karya Batang Kuis. The research method used in conducting this research is qualitative with content analysis as the research design. It is also known as the document analysis method.It is intended that readers will be able to learn about the types of grammar errors that occur when using Google Translate and also the most common errors. This research discovered that there are two addition errors in five narrative texts. The words are "after and who." There are two deletion errors. Those are deletion articles and translated people's names. Replacement errors are the most common, followed by a total of 17 errors. Among them are replacement errors because they cannot find the right equivalent, translating word for word, pronoun substitution errors, and translating people's names. The last is a misordering error. There are two misordering errors: that a word or a group of words is placed incorrectly in a sentence. It is intended that once readers understand this, they will avoid making the same errors and enhance their grammar translation knowledge and skills. Keywords: Google translate, Grammatical errors, Narrative text